Impact of variation in tariff costs on the adhesion of health professionals to PHC and on the retention of these professionals in needier regions. - Aguiar, Estêvão de Carvalho; Sousa, Amanda Antunes de; Ferreira, Cristiane Martins; Santos, Franklin (Brazilian Journal of Implantology and Health Sciences, 2025)
Introduction: The unequal distribution of health professionals in Brazil compromises the effectiveness of Primary Health Care (PHC), with financing being a key factor in the ability to attract and retain human resources in underserved areas. Objective: To analyze the scientific evidence on the impact of variations in tariff costs and financing models on the adherence and retention of health professionals in PHC. Methodology: Systematic literature review (PRISMA) with searches in the PubMed, SciELO, LILACS and Scopus databases for publications between 2015 and 2025. Studies that analyzed the correlation between financial factors and the allocation of professionals in PHC were included. Results: Fifteen publications were included. Direct remuneration was consistently associated with the initial attraction of professionals, while the quality of infrastructure and working conditions, both dependent on the unit's funding, were more relevant for long-term retention. The most proposed solutions in the literature included the creation of career plans (71.4%) and the restructuring of financing models with greater weighting for vulnerable areas (53.6%). Conclusion: PHC financing is a determining and multifaceted factor in the distribution of health professionals, and its strategic restructuring is essential to ensure equity in access to health.